Money in boom and slump: an empirical inquiry into British experience since the 1880s - Walters, A. A.; Institute of Economic Affairs (Great Britain) (London, Institute of Economic Affairs, 1969)
This book contains a non-working of markets, existing or potential, in the private and public sectors of the economy. The paper focused on economy policies and discussion in industry and government.
Bibliography: p. 55-56.
asm; 13/02/19
Loans
Keywords: Money; Quantity theory of money